(3cJGH aj PcQ GdEeGeI heGjJYdb HhLhHgG hLhGRgG hGdCMcGe GdYGeI hGdNGUI hEbGeI GdCOdI hGdHQGgjf Ydi UMJgGs ((3YeQ Hf eMeO Hf EHQGgje Hf YHOGddg GdhGSWi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CcQefG HeYQaJg hJhMjOg hCQTOfG Edi JbOjSg hJeLjOg hKHJfG Ydi gOGjJg hJSOjOg s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B135 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds